Analysis of Brand Loyalty Toward Ngopi Doeloe's Cafe in Bandung Using Brand Experience - Saraswati, Chisnia; Indriani, Mia T. D. (Journal of Business and Management, 2015)
Abstrack Nowadays many cafés was established in Bandung. Competitiveness between café to get market also increases. However, for now, it is not just get the new market but how to maintain the customer. So, brand loyalty becomes so important for company to invest in the future. Therefore, brand loyalty will be analyzed in this study. In addition, in this research also discuss about brand experience, what is the most influential between the four-dimensions of brand experience (sensory, affective, intellectual and behavioral) toward brand loyalty. The research object that will be taken is Ngopi Doeloe’s Café.. Ngopi doeloe is one of the famous café in Bandung whereas this cafe recently established. The conceptual framework that used in this study is taken from Brakus (2009). It explains about the influence of brand experience (sensory, affective, intellectual and behavior) toward brand loyalty. The methodology that will use in this research is non-probability method by using questionnaire as equipment research to get the data. The questionnaire contains statements of brand loyalty and brand experience as variables in this study. Then, the method to take a sample is using judgment sampling with taking sample size 155 Bandung’s people who ever consume coffee in Ngopi Doeloe. The data from questionnaire will be analyzed by multiple regression to know the influence brand experience toward brand loyalty. Meanwhile, the value of brand loyalty is determined by Ms. Excel. The conclusion showed that brand loyalty of Ngopi doeloe is low at 3,151 on a scale of 7. While the influence of the four dimensions of brand experience on brand loyalty are all positive and the results of multiple regression analysis showed that the most influential among the four dimensions of brand experience is behavioral experience. Keyword : Brand loyalty, Brand experience, Ngopi Doeloe’s café